ANALYSIS THE IMPACT OF HALAL SUPPLY CHAIN ON ENVIRONMENTAL AND SOCIAL SUSTAINABILITY - Kuncorosidi Kuncorosidi; Heru Setiawan; Devi Delviyani (STIESA Press, 2024)
Global awareness of climate change and its impacts has increased in recent years. Movements like